(untitled) - FAO (Rome, 1999)
The book deals with dissemination of the Code of Conduct and improvement of the planning process; enhancement of the harmonization between aquaculture development and environmental conservation; and use of the Code of Conduct to upgrade the economic value of aquaculture and to improve and stabilize trade in aquaculture products in the Mediterranean.
Keywords: fishery law and legislation